Pengaruh Petugas Tidak Resmi terhadap Kinerja Simpang Tak Bersinyal pada Persimpangan Jalan Wahid Hasyim - Jalan Selokan Mataram, Yogyakarta - Romadhona, Prima J.; Hakiki, Moh. Zuhdi Ridwan (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2020)
The traffic jam that occurred on Selokan Mataram Street specifically at the intersection of Selokan Mataran Street - Wahid Hasyim Street gave rise unofficial officers or commonly referred to as